2015
DOI: 10.15261/serdj.22.37
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Extraction of Soft Acid Metal Species Using MIDOA and Analogous Compounds

Abstract: The extractant, methylimino-bis-N,N'-dioctylacetamide (MIDOA), was used for the extraction of soft acid metals. It was found that MIDOA can extract not only Cr(VI), Mo(VI), W(VI), Tc(VII) and Re(VII), whose metals can form oxonium anions due to their high oxidation states, but also other metal cations, like MIDOA were also studied and discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Both extractants can be dissolved in n-dodecane and OC, so the values of D for these diluents are shown in Figure 2. between Pd(II) and the protons occurred at high concentrations of HNO 3 [6]. Consequently, the values of D decreased.…”
Section: Extraction Of Pdmentioning
confidence: 97%
See 2 more Smart Citations
“…Both extractants can be dissolved in n-dodecane and OC, so the values of D for these diluents are shown in Figure 2. between Pd(II) and the protons occurred at high concentrations of HNO 3 [6]. Consequently, the values of D decreased.…”
Section: Extraction Of Pdmentioning
confidence: 97%
“…Se may form oxyanions, of which the stable ions are SeO 3 2− and SeO 4 2− . Previous studies suggest that these oxyanions can be extracted using N-donor extractants [5,6,16]. In this study, we used two types of phenylenediamines (PDA and DMePDA, Figure 1) as complexants to form an extractable piazselenol, and the results are shown in Figure 7.…”
Section: Extraction Of Sementioning
confidence: 99%
See 1 more Smart Citation
“…According to the hard-soft acid-base (HSAB) principle [18], NTAamide has a strong bonding affinity with soft-acid metals. In this study, the masking effects on Mo, Tc, and the Pt group metals were studied in methylimino-N,N-dioctylacetamide (MIDOA) [17,[19][20] and NTAamide extraction using several water-miscible reagents. The main purpose was to establish the separation technique to strip metals from the organic phase and recover metals effectively.…”
Section: Introductionmentioning
confidence: 99%
“…based on the HSAB principle. Some papers reported that these extractants have strong extraction abilities for Mo, Tc, Re and Pd (MIDOA), and Pd, Ag, Au and Hg (TDGA) [13][14][15][16]. These extractants have the same central frame but with different donor atoms, however less work has been reported on the investigation of the role of O, N and S donors and comparison with their extractabilities In this work, using these extractants, the feature of metal-extraction on the periodic table by different donor atoms is investigated.…”
mentioning
confidence: 99%